Pride and prejudice - Austen, Jane (England : Penguin Books, 1972)
In early nineteenth century England, a spirited young woman copes with the suit of a snobbish gentleman as well as the romantic entanglements of her four sisters.
Keywords: Young women -- Fiction; Courtship -- Fiction; Domestic fiction